Dynamic Models of Multilingualism on the Territory of Western Ukraine - Наталія Михальчук; Павло Левчук; Ернест Івашкевич; Олександр Набочук (Психолінгвістика)
The purpose of the article is to study lexical units, with the help of which it becomes possible to build up the models of multilingualism, which are dominant among the population on the territory of Western Ukraine.